Avaliação da exposição ao ruído ocupacional em policiais militares do motopatrulhamento - Lima, Kelly Christine Silva de (2015)
The motorcycle patrol activity of the military Police is held in various environmental conditions with situations that cause discomfort and impair safety. The presence of occupational noise comes from sources such as urban traffic, the radio communicator, sirens, motorcycle and environmental noise, which added throughout the work day can cause the occurrence of hearing problems and induced hearing loss by noise. Thus, this work presents an investigation into how exposure to occupational noise of patrol activity affects the auditory system of motorcycle police officers during patrol activity. This case study was approved by the UFPB’s ethics committee in research. The data collection for this research was conducted in three stages: selection of police and application of occupational history questionnaires, audiometry and noise dosimetry according to ISO 9612:2009 recommendations. The study gathered 46 military police more than three years of service in motorcycle patrol activity and, no hearing aids history. The level of occupational noise is higher than the regulatory limits and the daily dose exceeds 400%. Hearing complaint was identified in 50% of police officers and more than 30% have hearing loss due to noise. The risk of aggravating these cases of hearing loss and the development of new cases is higher than 50% for these policemen with increased service life. Through these results, it is possible to suggest that exposure to occupational noise of motorcycle patrol activity can affect the auditory system of the military police, increasing the risk of hearing loss.